Answer:
-8..hope it helps you
Step-by-step explanation:
x=-8..Y=2
Yes because you have the follow the order of operations.
Answer:
and ![(CD)^2 + (BD)^2 = (CB)^2](https://tex.z-dn.net/?f=%28CD%29%5E2%20%2B%20%28BD%29%5E2%20%3D%20%28CB%29%5E2)
Step-by-step explanation:
Given
Bisector: CD
of Line AB
Required
Apply Pythagoras Theorem
From the question, CD bisects AB and it bisects it at D.
The relationship between AB and CD is given by the attachment
Considering ACD
From the attachment, we have that:
![Hypothenuse = CA](https://tex.z-dn.net/?f=Hypothenuse%20%3D%20CA)
![Opposite = CD](https://tex.z-dn.net/?f=Opposite%20%3D%20CD)
![Adjacent = AD](https://tex.z-dn.net/?f=Adjacent%20%3D%20AD)
By Pythagoras Theorem, we have
![(AD)^2 + (CD)^2 = (CA)^2](https://tex.z-dn.net/?f=%28AD%29%5E2%20%2B%20%28CD%29%5E2%20%3D%20%28CA%29%5E2)
Considering CBD
From the attachment, we have that:
![Hypothenuse = CB](https://tex.z-dn.net/?f=Hypothenuse%20%3D%20CB)
![Opposite = CD](https://tex.z-dn.net/?f=Opposite%20%3D%20CD)
![Adjacent = BD](https://tex.z-dn.net/?f=Adjacent%20%3D%20BD)
By Pythagoras Theorem, we have:
![(CD)^2 + (BD)^2 = (CB)^2](https://tex.z-dn.net/?f=%28CD%29%5E2%20%2B%20%28BD%29%5E2%20%3D%20%28CB%29%5E2)
Answer: B. 4x*2x^2+4x*(-2)+1*4x+1*(-2)
Step-by-step explanation: Hope this help :D